2020
DOI: 10.4269/ajtmh.19-0547
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Parasitemia and Nutritional Status during the Low Transmission Season in the Presence of Azithromycin Distribution among Preschool Children in Niger

Abstract: The relationship between malaria and malnutrition is complicated, and existence of one may predispose or exacerbate the other. We evaluated the relationship between malaria parasitemia and nutritional status in children living in communities participating in a cluster-randomized trial of biannual azithromycin compared with placebo for prevention of childhood mortality. Data were collected during the low malaria transmission and low food insecurity season. Parasitemia was not associated with weight-for-height Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In our study, we hypothesized that malaria infection (prolonged asymptomatic parasitemia in the malaria endemic region) poses a risk for malnutrition in children. However, most malaria-malnutrition studies investigated this phenomenon in children of age five years and below, with a perspective that malnutrition is the underlying risk for malaria since poor nutritional status leads to weak immunity [14,34]. Malaria was significantly associated with stunting in our .…”
Section: Discussionmentioning
confidence: 94%
“…In our study, we hypothesized that malaria infection (prolonged asymptomatic parasitemia in the malaria endemic region) poses a risk for malnutrition in children. However, most malaria-malnutrition studies investigated this phenomenon in children of age five years and below, with a perspective that malnutrition is the underlying risk for malaria since poor nutritional status leads to weak immunity [14,34]. Malaria was significantly associated with stunting in our .…”
Section: Discussionmentioning
confidence: 94%
“…A previous study evaluating the relationship between malaria and nutritional status in Niger found no evidence of effect modification of the relationship between communities receiving biannual mass azithromycin distribution to children compared with placebo. 16 Although azithromycin has antimalarial properties in vivo 5 and has been shown to reduce parasitemia when administered to entire communities of children, 7 it is a weak antimalarial and may only have limited antimalarial effects when administered at the individual level. The primary analysis did not find evidence of a difference in weight gain between children receiving azithromycin and amoxicillin, 17 and this result does not appear to be moderated by malarial parasitemia.…”
Section: Discussionmentioning
confidence: 99%
“…Potential confounders of the association between malnutrition and malaria infection were selected a priori using a directed acyclic graph and based on previous literature. 9 , 23 Covariates that were included in multivariable models were sex, age (in months), breastfeeding status, maternal education, and study treatment (azithromycin versus placebo). Age (in months) was not included in the models that assessed effect modification, as the binary measure of age was included in the interaction term.…”
Section: Methodsmentioning
confidence: 99%